Urban Freight and Port Cities - Blanco, Edgar E. (World Bank, Washington, DC, 2014)
This note explores issues within the urban logistics and port-cities thematic pillar. It is one of three focus areas, or thematic pillars, for the multi-donor trust fund for sustainable logistics (MDTF-SL). The goal of this pillar is to finance activities that will assist developing countries in two areas; addressing urban congestion resulting from retail distribution of goods, and improving the sustainable design and operation of port-cities. Activities under this pillar will concentrate on reducing congestion and pollution by focusing on the efficient distribution of goods in urban environments. Additional emphasis will be placed on the urban planning tools and investments required for port-cites to address sustainability issues endemic to densely populated economies serving as either a local or regional transport hubs.